ANALISA DAN PERANCANGAN SISTEM INFORMASI KEHADIRAN DAN KEPEGAWAIAN BERBASIS PT. GRAHA KABELINDO - Sival Mukaromahh; Inna Sabily Karima (Ensiklopedia of Journal, 2019)
Employee attendance and payroll systems are things that matters for every company, because they can simplify the implementation.But in this case the implementation of the system at the company PT. Graha Kabelindo still using a simple system such as ms. Excel so there are still obstacles that happen ,such as in employee data management, attendance, overtime, filing leave, and payroll. In the end the author was interested in creating a web-based attendance and payroll system design using the PHP programming language and MySQL database and using the waterfall method. The expected results hopefully can simplify reporting online attendance and payroll for all employees.